Ag2O Nanoparticles as a Candidate for Antimicrobial Compounds of the New Generation - Sergey V. Gudkov; Dmitriy A. Serov; Maxim E. Astashev; Anastasia A. Semenova; Andrey B. Lisitsyn (MDPI AG, 2022)
Antibiotic resistance in microorganisms is an important problem of modern medicine which can be solved by searching for antimicrobial preparations of the new generation. Nanoparticles (NPs) of metals and their oxides are the most promising candidates for the role of such preparations. In the last few years, the number of studies devoted to the antimicrobial properties of silver oxide NPs have been actively growing. Although the total number of such studies is still not very high, it is quickly increasing. Advantages of silver oxide NPs are the relative easiness of production, low cost, high antibacterial and antifungal activities and low cytotoxicity to eukaryotic cells. This review intends to provide readers with the latest information about the antimicrobial properties of silver oxide NPs: sensitive organisms, mechanisms of action on microorganisms and further prospects for improving the antimicrobial properties.